Association between different hemoglobin glycation index and prognosis in patients with a first diagnosis of acute myocardial infarction: a retrospective study based on the MIMIC-IV database - Dong Chen; Dong Chen; Ben Hu; Xing-hua Chen; Xing Wei; Jun Feng; Ze-ping Hu (Frontiers in Cardiovascular Medicine)
BackgroundThe hemoglobin glycation index (HGI) is defined as the difference between the observed and predicted values of glycosylated hemoglobin (HbA1c), which is closely associated with a variety of poor prognoses. However, the relationship between HGI and short-term mortality risk in patients with a first diagnosis of acute myocardial infarction (AMI) remains unclear. This study aims to provide a better understanding of the relationship between HGI and mortality risk in patients with a first diagnosis of AMI.MethodsWe conducted a cohort study using data from 1,961 patients with a first diagnosis of AMI from the Medical Information Mart for Intensive Care IV (MIMIC-IV; version 2.2) database. Patients were divided into four groups based on HGI quartiles. A Cox proportional hazards model and a two-segmented Cox proportional hazards model were used to elucidate the non-linear relationship between HGI in patients with a first diagnosis of AMI and mortality.ResultsOf the surveyed population, 175 patients (8.92%) died within 90 days, and 210 patients (10.71%) died within 180 days. A low HGI was significantly associated with 90-day mortality [HR, 1.99; 95% CI (1.22, 3.08); P < 0.001] and 180-day mortality [HR, 1.74; 95% CI (1.18, 2.43); P < 0.001] in patients with a first diagnosis of AMI in the completely adjusted Cox proportional risk model, showing a non-linear correlation with an inflection point at 0.16 and 0.44. In the subgroup analysis, patients with prediabetes mellitus (pre-DM) and lower HGI levels had increased 90-day [HR, 8.30; 95% CI (2.91, 23.68)] and 180-day mortality risks [HR, 6.84; 95% CI (2.86, 16.34)].ConclusionThere is a significant correlation between HGI and all-cause mortality in patients diagnosed with AMI, especially those with lower HGI. HGI can serve as a potential indicator for evaluating the 90 and 180-day death risk of such patients.